Comparison of viscoelastic test results from blood collected near simultaneously from the jugular and saphenous veins in cats. Issue 6 (June 2021) - Fudge, James Mack; Cano, Katherine S; Page, Bernie; Jeffery, Unity
Objectives: The aim of this study was to compare viscoelastic test results from samples collected from a jugular vein using a 20 G needle and a medial saphenous vein using a 22 G needle in cats presenting for elective ovariohysterectomy (OHE) or castration. Methods: Forty apparently healthy cats (20 males and 20 females) presenting for elective OHE or castration were included in a prospective study observing viscoelastic test results from central and peripherally collected whole blood. Cats were anesthetized during blood collection with a standardized protocol including buprenorphine, ketamine, dexmedetomidine and isoflurane. Blood samples from jugular and saphenous veins were collected near simultaneously. Viscoelastic evaluations of whole blood were performed using a point-of-care device measuring clot time (CT), clot formation time (CFT), alpha angle (α), maximum clot formation (MCF), and amplitude at 10 and 20 mins (A10 and A20, respectively). Viscoelastometry continued post-clot time to determine a lysis index at 30 and 45 mins (LI30 and LI45, respectively) to assess fibrinolysis. Results: Studied cats had a median age of 18 months (range 5 months to 5 years) and a median weight of 3.6 kg (range 2.7–5.9 kg). A total of 80 samples were available for analysis. While lysis indices were not different, viscoelastic measures of coagulation differed between sampling sites (CT, P <0.005; CFT, P = 0.01; α, P <0.05; MCF, P <0.0005; A10, P <0.0005; A20, P <0.0005). Conclusions and relevance: Viscoelastic results from jugular venous blood samples appear to be more hypercoagulable than those collected from the medial saphenous vein, suggesting that the same site should be used consistently for serial monitoring or for collecting study data.